Aneurysms Causes, Diagnosis and Treatment (The Peerian Journal, 2025)
Aneurysms are localized dilations of blood vessels that pose a significant risk of rupture and lifethreatening hemorrhage. The development of aneurysms is multifactorial, with common etiologies including atherosclerosis, hypertension, genetic predisposition, infection, and trauma. Aneurysms can occur in various vascular territories, most notably in the aorta and cerebral arteries. Early and accurate diagnosis is critical and relies on advanced imaging techniques such as computed tomography (CT), magnetic resonance imaging (MRI), and ultrasonography. Management strategies depend on the size, location, and risk of rupture and range from careful monitoring to surgical or endovascular intervention. Recent advancements in endovascular techniques have significantly improved patient outcomes, offering less invasive alternatives to traditional open surgery. This article reviews the pathophysiology, risk factors, diagnostic modalities, and current treatment approaches for aneurysms, emphasizing the importance of early detection and personalized care to reduce morbidity and mortality.